2022
DOI: 10.12821/ijispm060404
|View full text |Cite
|
Sign up to set email alerts
|

The roles of top management and users in strategic IS planning: a perspective of SMEs

Abstract: Research on the strategic Information Systems (IS) planning is typically concentrated on large firms. However, the outcomes of this research may not be sufficient to adequately apply to Small and Medium Enterprises (SMEs). Responding to the limited body of work in SMEs with respect to strategic IS planning, this research aims to fill the gap in the body of literature. Having limited resources available, financially and technically, strategic IS planning is getting more crucial for SMEs. Prior work suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…So, it seems that creative SMEs with at least one woman as managers can affect positively on their productivity, in addition to the use of DTs. Thus, our results are consistent with previous studies [3,66,70,71,72].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…So, it seems that creative SMEs with at least one woman as managers can affect positively on their productivity, in addition to the use of DTs. Thus, our results are consistent with previous studies [3,66,70,71,72].…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, it seems that large manufacturing firms with low proportion of female managerial position may be prone to not adopting these DTs. Thus, our results are consistent with previous studies [3,65,70,72]. At this point, it is important to mention that the RMSE in both models (3 and 4) according to labour productivity shows satisfactory significance (0.998 and 1.157) and the R square (0.27) is slightly moderate [75], respectively.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also relate to Cravotta and Grottke [2] who state that family firms need to prepare themselves for long-term changes brought upon them by digitalization and that those changes also affect these firms' operational activities. These changes also touch upon operational matters [109], [110] which is relevant insofar as business succession is accompanied by very hands-on issues, as demonstrated in this study's results. We find that the succession process can delay the introduction of those changes and therefore a prolonged family-external business succession demonstrates a challenge for SMFB that could impede their competitiveness.…”
Section: Discussion Of Resultssupporting
confidence: 53%
“…With digitalization challenges facing various organization, it is imperative that they equip themselves with various capabilities including both technology and innovation related [69]. Extant studies have identified the existence of a positive relationship between learning and innovation in organizations [3,70,71].…”
Section: Learning For Innovationmentioning
confidence: 99%